Evaluation of the determinants of growing current account deficit - Garšvienė, Lina; Butkus, Mindaugas (Socialiniai tyrimai, 2014)
The objective of the paper is to identify and generalize the factors determining the growth of current account deficit and select the periods of growing current account deficit and evaluate their determinants. The results of the analysis confirmed the growing current account deficit reaching from 3% to 30% of GDP in different developing and developed countries. The results showed that growing current account deficit is strongly determined by domestic demand and market prices; however, other factors such as national openness, international movement of capital, and the condition of world market have no significant impact.